Pengaruh Peer Group Support terhadap Peningkatan Motivasi ADL dengan Mandiri pada Pasien Pasca Stroke : Pengaruh Peer Group Support terhadap Peningkatan Motivasi ADL dengan Mandiri pada Pasien Pasca Stroke - Sugiyarto Sugiyarto; Siti Khadijah (Universitas Islam Jember, 2021)
Problems often experienced by stroke patients are muscle weakness and inability to move, this can cause problems in carrying out activity of daily living (ADL) for post-stroke patients, because of limited movement and need the full help of others These patients feel useless and make them dissatisfied in living their lives, therefore it is necessary to take action to increase patient motivation, namely peer group support. The purpose of this study was to determine the effect of peer group support on ADL motivation in post-stroke patients. This study used a quasi-experimental research design using one group Pre-Test-Post Test. The sampling technique in this study was consecutive sampling. The number of samples in this study were 16 post-stroke patients. The intervention in this study was Peer Group Support in post-stroke patients.The giving of Peer Group Support measures has an effect on increasing the motivation to do ADL independently of post-stroke patients at the Sibela and Gambir Sari Public Health Center, Surakarta with a p value of 0.001. Providing Peer Group Support for post-stroke patients to increase motivation in performing ADL independently, actions can be done more than once or programmed to maintain the quality of motivation. Keywords: Peer Group Support, ADL Motivation, Post Stroke Patients